Effect of porcine and equine FSH on embryo quality in Sahiwal cows - PRASAD, SHIV; MAURYA, S N (The Indian Journal of Animal Reproduction, 2023)
The present study revealed significantly (P< 0.01) higher embryo recovery and their quality using FSHpthan FSH-E. The use of follicle stimulating honnone from porcine source has been found better in comparison tofollicle stimulating hormone from equine sources for super ovulating indigenous cattle.
Keywords: Superovulation; FSH; embryo; cattle